Clusterrandomisierte kontrollierte Untersuchung eines Stressbewältigungs-Trainings in der gymnasialen Oberstufe - Eppelmann, Lena; Parzer, Peter; Lenzen, Christoph; Bürger, Arne; Haffner, Johann; Resch, Franz; Kaess, Michael (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2018)
Objective: One ﬁfth of German adolescents show elevated levels of mental health problems. The development of mental health problems is often closely related to experiences of stress. Hence, fostering competences in coping with stress offers an approach for counteracting the development of psychological problems. The aim of the present study is to test a stress management training of 3 x 90 minutes in a German high school, 11th grade. Method: A cluster-randomized, controlled design was used. The primary outcome was stress. Secondary outcome criteria were knowledge about stress, coping behaviour, emotional and behavioural problems as well as health-related quality of life. Students from twenty-one courses from four schools participated in the study. Results: The sample comprised 286 students (58.25 % girls; mean age 16.58 ± 0.65). Changes in stress levels from pre- to post-evaluation did not differ signiﬁcantly between intervention and control group. With regard to secondary criteria, apart from a signiﬁcant increase in knowledge no further effects were observed. An exploratory moderation analysis hints at a positive association between baseline levels of stress and effectiveness of the training. Conclusions: The results question whether the universal application of a brief cognitive behavioural intervention is appropriate to prevent stress in this population. Future research should, inter alia, investigate the potential of indicated prevention regarding stress.